Development of nutrition practice guidelines and its efficacy in combination with N3-LCPUFA supplement for the management of childhood obesity - Md. Yusop, Nor Baizura (2017)
The worldwide prevalence of overweight and obese children has steadily increased from 4.7% in 1990 to 6.7% in 2012. Dietary intake and physical activity modification are the first line of treatment for obesity in any weight management programme. However, both are highly dependent on the child’s ability to follow recommendations. A combination of long-chain polyunsaturated fatty acids (n-3 LCPUFA), docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and lifestyle modification showed positive results in weight management among adults. There were three phases in the study. Phase I was aimed to develop Nutrition Practice Guidelines (NPG) for the Management of Childhood Obesity; the aim of phase II was to evaluate the effectiveness of the NPG; and phase III was aimed to determine the effect of Stage-based Lifestyle Modification for the Management of Childhood Obesity and n-3 LCPUFA supplementation on body composition, biochemical profile, diet and physical activity of obese children. Phase I had two parts. In part I, a survey was conducted to assess dietitians’ current practices in the management of childhood obesity. In part II, a survey on the use of practice guidelines by dietitians in other countries was conducted. A comparison of the current practices of local dietitians and practice guidelines used by dietitians in other countries was conducted to identify relevant practice components for the development of the NPG. In Phase II, a pilot study including 40 obese children aged 7–11 years old was conducted for a duration of 24 weeks. The intervention group received the NPG, while the control group received standard treatment for the management of childhood obesity. Outcome measurements of the intervention study including stages of change (SOC), dietary intake, body composition and physical activity were taken at baseline and every four weeks. None of the dietary intake outcomes had significantly different between the groups, while physical activity mean change difference between groups was significant (p<0.05). The post-treatment mean of weight and WC between the intervention group and the control group also did reach significance level (p<0.05). Overall, the results demonstrated that the developed NPG are effective in managing childhood obesity. In phase III, 37 obese children were included in a randomised controlled trial of effects of n-3 LCPUFA supplementation for the management of childhood obesity. Both groups received stage-based lifestyle modification, and the intervention group was also required to consume n-3 LCPUFA for a duration of 16 weeks. Outcome measurements of the study including body composition, biochemical profile, dietary intake and physicalactivity were taken at baseline, week 16 and week 24. The results showed that none of the differences in dietary intake, physical activity and body composition outcomes did reach significance level (p<0.05) between groups. Only, LDL was significantly different between the two treatments. However, there were interactions of time and group for physical activity, weight, HDL, LDL and TC-HDL, which indicated that the values changed over time due to the treatments. N-3 LCPUFA is effective in improving the lipid profile but not dietary intake, physical activity and body composition of obese children.